Calcium isotope fractionation between aqueous compounds relevant to low-temperature geochemistry, biology and medicine - Moynier, Frédéric (Sci Rep, 2017)
Stable Ca isotopes are fractionated between bones, urine and blood of animals and between soils, roots and leaves of plants by >1000 ppm for the (44)Ca/(40)Ca ratio. These isotopic variations have important implications to understand Ca transport and fluxes in living organisms; however, the mechanisms of isotopic fractionation are unclear. Here we present ab initio calculations for the isotopic fractionation between various aqueous species of Ca and show that this fractionation can be up to 3000 ppm. We show that the Ca isotopic fractionation between soil solutions and plant roots can be explained by the difference of isotopic fractionation between the different first shell hydration degree of Ca(2+) and that the isotopic fractionation between roots and leaves is controlled by the precipitation of Ca-oxalates. The isotopic fractionation between blood and urine is due to the complexation of heavy Ca with citrate and oxalates in urine. Calculations are presented for additional Ca species that may be useful to interpret future Ca isotopic measurements.